The Effects of Hip Joint Movement on the Lumbo-pelvic Muscle Activities and Pelvic Rotation During Four-point Kneeling Arm and Leg Lift Exercise in Healthy Subjects - Nam-goo Kang; Won-jeong Jeong; Min-ju Ko; Jae-seop Oh (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2023)
Background: The gluteus maximus (GM) muscle comprise the lumbo-pelvic complex and is an important stabilizing muscle during leg extension. In patients with low back pain (LBP) with weakness of the GM, spine leads to compensatory muscle activities such as instantaneous increase of the erector spinae (ES) muscle activity. Four-point kneeling arm and leg lift (FKALL) is most common types of lumbopelvic and GM muscles strengthening exercise. We assumed that altered hip position during FKALL may increase thoraco-lumbar stabilizer like GM activity more effectively method. Objects: The purpose of this study was investigated that effects of the three exercise postures on the right-sided GM, internal oblique (IO), external oblique (EO), and multifidus (MF) muscle activities and pelvic kinematic during FKALL. Methods: Twenty eight healthy individuals participated in this study. The exercises were performed three conditions of FKALL (pure FKALL, FKALL with 120° hip flexion of the supporting leg, FKALL with 30° hip abduction of the lifted leg). Participants performed FKALL exercises three times each condition, and motion sensor used to measure pelvic tilt and rotation angle. Results: This study demonstrated that no significant change in pelvic angle during hip movement in the FKALL (p > 0.05). However, the MF and GM muscle activities in FKALL with hip flexion and hip abduction is greater than pure FKALL position (p < 0.001). Conclusion: Our finding suggests that change the posture of the hip joint to facilitate GM muscle activation during trunk stabilization exercises such as the FKALL.